Reverse Peroneal Artery Flap—A Workhorse Flap for Reconstruction of Large, Distal Defects of Ankle and Foot - Palukuri, Lakshmi; Ireni, Raja Kiran Kumar Goud; Jabbar, Faiyaz Abdul; Nair, Shaleena Sukumaran; Jambula, Pranav Reddy; Kommu, Vijaybabu (Indian Journal of Plastic Surgery, 2022)
Background Reconstruction of large foot and ankle defects is a difficult task due to less available local soft tissue and more critical from functional point of view. To overcome the limitations associated with locoregional flaps and free flaps, reverse peroneal artery (RPA) flap was selected and its usefulness in reconstruction of distal large defects of the ankle and foot and its complications were studied.Materials and Methods This is a prospective observational study done in 20 patients treated as cohort within 2 years and 8 months from January 2018 to August 2020. Large defects of foot and ankle were reconstructed with RPA flap and evaluated for its usefulness. Three cases were evaluated with computed tomography angiography postoperatively, to assess the vascular pattern.Conclusion RPA flap is a versatile and very reliable flap for the reconstruction of large and distal defects of foot and ankle. It is safely done in children and in acute trauma without any major complications.
Keywords: reverse peroneal artery flap; reconstruction of foot and ankle defects; peroneal perforator fasciocutaneous flaps; reverse flow flaps; CT peripheral angiogram; peroneal artery communications